Geopolymer 3D printing: a comprehensive review on rheological and structural performance assessment, printing process parameters, and microstructure - Barve, Prasad; Bahrami, Alireza; Shah, Santosh (Frontiers in Materials, 2023)
Geopolymers are under scrutiny as a sustainable alternative to cement in 3D printing for eco-friendly construction. Geopolymer 3D printing (G3DP) holds promise for green construction and advanced manufacturing. This study addresses G3DP’s rheological properties, printability, and microstructure analysis. Results indicate the pivotal role of the rheological properties in the printability, encompassing parameters like the pumpability, extrudability, and shape retention. Lower viscosity and appropriate yield stress are crucial. The structural performance of G3DP, given its inherent anisotropic nature and assessment techniques, is scrutinized. Process variables such as nozzle design and print speed and interval affect the printability, buildability, and structural properties. Research on the parameters’ optimization is necessary. Additionally, evaluation techniques for the G3DP’s rheological and structural behaviors require standardization. Understanding the G3DP’s rheology is paramount for the successful 3D printing construction. Findings offer quantitative insights into the importance of the rheological properties for the printability and structural performance. The microstructural analysis uncovers the porosity and density disparities compared to traditional geopolymers. This comprehensive review provides valuable insights for researchers and practitioners to enhance the G3DP’s application as a futuristic sustainable construction material.